A memoir of my former self a life in writing - Mantel, Hilary 1952-2022 (Henry Holt and Company, 2023)
"A posthumous collection of journalism and other writings by Hilary Mantel, revealing in spectacular breadth the beloved writer's cutting wit and singular voice on books, films, the royals, and her own life"--
Keywords: Mantel, Hilary -- 1952-2022; Mantel, Hilary / 1952-2022; Women / Social conditions; Women novelists, English / Biography; Novelists, English / Biography; Women journalists / England / Biography; English essays; Femmes / Conditions sociales; Essais anglais; Romancières anglaises / Biographies; Romanciers anglais / Biographies; Femmes journalistes / Angleterre / Biographies; Essays; Biographies; Autobiografie